Technical Solution for Complex Layer-by-Layer Tillage with Soil Formation Turnover - Belousov Sergey (EDP Sciences, 2021)
The paper deals with the issues of mechanization of main till-age with the soil formation turnover, the problems of traction resistance and possible solutions. The article has an analytical character, the analysis of ways and means of a possible solution to the problem of reducing traction resistance is given based on the results of studying the works of leading scientists in this direction. A technical solution for improving the design of the dump plow body is proposed. The technical process of working with the use of proposed working bodies is also justified. In conclusion, the main results achieved so far are presented.